Effect of climate finance on adaptation in the southwestern coastal region of Bangladesh. Issue 7 (2nd October 2020) - Hussain, Firdaus Ara; Ahmad, Mokbul Morshed
ABSTRACT: This article examines the effectiveness of climate finance on the engagement of poor and marginal households in adaptation measures. Data from 240 climate finance recipient households and 120 non-climate finance households in the south-western coast of Bangladesh were collected through a field survey. The results indicated that while recipient households engaged in more adaptation measures, they also spend more on adaptation from their income, savings and even loans. Some underlying constraints for households to access climate finance were identified. Finally, mislabelling regular poverty reduction activities as adaptation measures limits the support for climate finance at the household level.